Steady state signatures in the time domain for nonintrusive appliance identification (2015)
Smart Grid paradigm promotes advanced load monitoring applications to support demand side management and energy savings. Recently, considerable attention has been paid to Non-Intrusive Load Monitoring to estimate the individual operation and power consumption of the residential appliances, from single point electrical measurements. This approach takes advantage of signal processing in order to reduce the hardware effort associated to systems with multiple dedicated sensors. Discriminative characteristics of the appliances, namely load signatures, could be extracted from the transient or steady state electrical signals. In this paper the effect of impact factors that can affect the steady state load signatures under realistic conditions are investigated: the voltage supply distortion, the network impedance and the sampling frequency of the metering equipment. For this purpose, electrical measurements of several residential appliances were acquired and processed to obtain some indices in the time domain. Results include the comparison ofdistinct scenarios, and the evaluation of the suitability and discrimination capacity of the steady state information.